2004
DOI: 10.1016/j.cellbi.2004.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry of nuclear and nucleolar structures in a CaCo‐2 cell line

Abstract: The number of the nucleoli in a CaCo-2 cell nucleus does not generally depend on the quantity of DNA in the nucleus, but nucleolar DNA content is directly proportional to total nuclear DNA. However, in multinucleolar cells (three or more nucleoli), the nucleolar DNA content increases after 96 h incubation in culture without concomitant quantitative changes in nuclear DNA. The percentage of multinucleolar cells and the average number of nucleoli per nucleus increase with increasing incubation time. After 72 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…The cDNA of one Caco-2 cell clone (clone #1) was therefore further analyzed via bacterial cloning of the ATP7B exon 2 PCR product. Sequence analysis of the bacterial clones (n = 19) suggested a compound mutation consisting of altogether three deletions (p.L394F_A395del, p.L394FfsX9 and p.E396KfsX11) corroborating the reported polyploidy of the Caco-2 cell line (S3 Table) [25]. Importantly, a wildtype sequence could not be observed in the bacterial clones.…”
Section: Generation Of a Human Atp7b Crispr/cas9 Knockout Intestinal Cell Linesupporting
confidence: 59%
“…The cDNA of one Caco-2 cell clone (clone #1) was therefore further analyzed via bacterial cloning of the ATP7B exon 2 PCR product. Sequence analysis of the bacterial clones (n = 19) suggested a compound mutation consisting of altogether three deletions (p.L394F_A395del, p.L394FfsX9 and p.E396KfsX11) corroborating the reported polyploidy of the Caco-2 cell line (S3 Table) [25]. Importantly, a wildtype sequence could not be observed in the bacterial clones.…”
Section: Generation Of a Human Atp7b Crispr/cas9 Knockout Intestinal Cell Linesupporting
confidence: 59%
“…The nucleolar DNA content is an indicator of functional condition and of cellular proliferation degree (Trére 2000; Karalyan et al. 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The nucleolar DNA content is an indicator of functional condition and of cellular proliferation degree (Trére 2000;Karalyan et al 2004). In the old gerbil prostate, the number of nucleolar corpuscles increased slightly in PINs and carcinoma, while in prostatic stromal hyperplasia almost 70% of the nuclei did not present evident nucleoli.…”
Section: Discussionmentioning
confidence: 99%
“…The nucleolus/nucleus ratio showed that dimensional variations undergone by the nuclei are accompanied by the nucleoli, which have a functional complementation among these organelles. Nucleolar DNA content is an indicator of functional condition and the degree of cellular proliferation (Karalyan et al,2004). Studies have shown that quantitative analysis of AgNOR proteins provides additional information concerning the biological behavior of tumors, being an independent prognostic factor (Ceccarelli et al,2000; Öfner,2000).…”
Section: Discussionmentioning
confidence: 99%